Krisis Citra Penyelenggaraan Event Jakarta Fair untuk Mengembalikan Konsep Merakyat - Evelina, Lidia Wati (Bina Nusantara University, 2014)
Research goal is to analyze the crisis of event implementation image of Jakarta Fair 2013, done by JIExpo which changing from people orientation to business orientation. This research is motivated by the desire of the city government to restore the original concept of the event held for the people. Research used qualitative method approach to find out more about the communications made by the city government. Information and data were obtained through interviews conducted by the visitor and direct observation in the field. Triangulation was used to test the validity of research data. Source selection was done using purposive sampling technique. The analysis used the analysis of the reduction is to collect, dispose of, and process the information and then displays the data and drawing conclusions. Results achieved that the promotional activities undertaken by JIEXPO are able to attract many people's attention to come even though it is located quite far away and charged. However, the party criticized the government organization that is not after the populist concept. Conclusion from the research organization of this annual event remains one of alternative entertainment for society in general and in particular to the people of Jakarta and surrounding areas. However, the need to accommodate the delivery of PT JIEXPO small businesses to be able to participate in the annual event. There needs to be an open conversation that is a win-win solution between PT JIExpo with the city government.